INTERNALISASI NILAI-NILAI KARAKTER PESERTA DIDIK DALAM PEMBELAJARAN TAHSIN DAN TAHFIDZ AL-QUR’AN DI MA TAHFIZHIL QUR’AN YAYASAN ISLAMIC CENTRE SUMATERA UTARA - Duma Mayasari (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
Al-Qur'an as a guide to Muslim life that we must read and practice it.Tahsin and tahfidz learning methods are one of the ways taken by someone in theprocess of reading and memorizing the Qur'an correctly and correctly so that it isalways remembered and can speak it fluently outside the head without seeing thetext of the Qur'an. This study uses a qualitative approach. While the method ofcollecting data using observation or observation, interviews, field notes and studydocuments. The results of this study can be stated that through tahsin learning and tahfidz Al-Qur'an in the Islamic School of North Sumatra Islamic Madrasah Aliyah can form students who have good morals or morals from the learningprocess. In the learners will be embedded a sense of sincerity, discipline, honesty,patience, trustworthiness, religious, hard work, istiqomah and responsible that isapplied in everyday life because it has permeated and inspired the meaning of theQur'an.